2016
DOI: 10.11114/jets.v5i1.1987
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sprint Reaction and Visual Reaction Times of Athletes in Different Branches

Abstract: The aims of th competing in various branch group of this meter for sprin all tests. SPSS Post Hoc test Study results basketball, vo averages of s players were b and sprint reac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Reaction values of football players were detected to be better than volleyball players and handball players [17]. Moreover, in a study that investigated the sprint reaction and visual reaction times of athletes from different branches (volleyball, basketball, handball) authors reported that the best visual reaction time score belonged to handball players, while volleyball players had the worst score [18]. In our study, when branches were compared among each other according to MRT of 10 different trials, arm wrestlers and volleyball players were found to have the shortest MRT among others.…”
Section: Discussionmentioning
confidence: 99%
“…Reaction values of football players were detected to be better than volleyball players and handball players [17]. Moreover, in a study that investigated the sprint reaction and visual reaction times of athletes from different branches (volleyball, basketball, handball) authors reported that the best visual reaction time score belonged to handball players, while volleyball players had the worst score [18]. In our study, when branches were compared among each other according to MRT of 10 different trials, arm wrestlers and volleyball players were found to have the shortest MRT among others.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the phrase "reactive agility" has been introduced to differentiate the tests with or without response to a stimulus [5]. To the best of our knowledge, there have only been a few studies in which an agility test was used that included the cognitive component [9][10][11][12]. The CODS tests are more common, and their structure has been well investigated [1,2,5].…”
Section: Introductionmentioning
confidence: 99%
“…As it is a team and struggling sport involving control, it requires high-level sportive performance such as durability, strength, pace, and agility. Today, this requires footballers from all positions to have many motor abilities at a high level (Köklü, Özkan, Alemdaroğlu, & Ersöz, 2009;Akyüz, Uzaldi, Akyüz, & Doğru, 2016;Sevim, 2006;Tatlici & Cakmakci, 2019). In addition, it involves various complex movements within the game such as walking, jogging, dribbling with sprint, shooting, and passing (Eniseler, 1994;Boyle 2004) and these days small times make teams or players winner .…”
Section: Introductionmentioning
confidence: 99%